Willingness to pay for marine-based tourism within the Ponto do Ouro Partial Marine Reserve, Mozambique - Daly, Clare Amelie Keating (Rhodes University, Faculty of Commerce, Department of Economics and Economic History, 2014)
Marine and coastal ecosystems face widespread degradation largely because market failure hides the economic value of the goods and services provided by them. Marine protected areas (MPAs) can serve as a structure that ensures the continuing function of marine and coastal ecosystem goods and services. Yet, to be effective and sustainable, MPAs must be able to prove their economic worth and generate revenue. User-fees are a common system used to partially finance multi-use MPAs. This study applies contingent valuation as a method of economic valuation within an MPA in southern Mozambique. The objectives of this study are to determine the willingness to pay of combined user groups and of individual user groups for use of the Ponta do Ouro Partial Marine Reserve and to investigate the potential for the reserve to increase revenues for conservation through the implementation of a user-fee for marine based activities. The payment card contingent valuation method was employed to determine willingness to pay of dolphin swim tourists, scuba divers and fishermen. Data was collected by face-to-face interviews of 120 respondents within two popular tourist locations in the PPMR. Results show that visitors within the PPMR are mainly South Africans, loyal to the area. Probit and OLS regressions were used to determine the effects of various independent variables on willingness to pay. Results from the Probit model indicate that African residency, activity and environmental awareness were significant factors that influenced visitors being WTP more than R20 per person per day as a user fee within the PPMR. The OLS model examined independent variables that influenced visitors being willing to pay as well as the impact of the variables on the amount visitors were willing to pay. The OLS model found income, African residency and environmental awareness to be significant factors influencing visitors being willing to pay. The mean WTP was R43.75 per person per day. Using data supplied by the PPMR, conservative estimated annual revenues based on the implementation of this fee amount would range between R1.46m "“ R 3.3m.
Keywords: Ponto do Ouro Partial Marine Reserve; Marine ecotourism -- Mozambique; Marine ecotourism -- Economic aspects -- Mozambique; Marine ecotourism -- Mozambique -- Marketing; Ecotourism -- Economic aspects -- Mozambique; Coastal zone management -- Mozambique; Marine resources conservation -- Mozambique